2017
DOI: 10.1021/acs.nanolett.6b05354
|View full text |Cite
|
Sign up to set email alerts
|

Competing Gap Opening Mechanisms of Monolayer Graphene and Graphene Nanoribbons on Strong Topological Insulators

Abstract: Graphene is a promising material for designing next-generation electronic and valleytronic devices, which often demand the opening of a bandgap in the otherwise gapless pristine graphene. To date, several conceptually different mechanisms have been extensively exploited to induce bandgaps in graphene, including spin-orbit coupling and inversion symmetry breaking for monolayer graphene, and quantum confinement for graphene nanoribbons (GNRs). Here, we present a multiscale study of the competing gap opening mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…where the first solutions are given by ε = ±3∆ 0 t. Therefore, the size of the gap is given by 6∆ 0 t, which coincides with the gap for an infinite Kek-O distorted graphene sheet 22,25 . This last result applies only to zigzag GNR, for the Kek-O armchair GNRs the gap turn to be considerable smaller 29,40 . Notice that there is an entirely flat band at zero energy, this band will not contribute to transport since it has vanishing group velocity 41 .…”
Section: B Kek-o Zigzag Graphene Nanoribbonsmentioning
confidence: 89%
See 1 more Smart Citation
“…where the first solutions are given by ε = ±3∆ 0 t. Therefore, the size of the gap is given by 6∆ 0 t, which coincides with the gap for an infinite Kek-O distorted graphene sheet 22,25 . This last result applies only to zigzag GNR, for the Kek-O armchair GNRs the gap turn to be considerable smaller 29,40 . Notice that there is an entirely flat band at zero energy, this band will not contribute to transport since it has vanishing group velocity 41 .…”
Section: B Kek-o Zigzag Graphene Nanoribbonsmentioning
confidence: 89%
“…For instance it has been pointed out that a Kek-O distortion allows the realization of charge fractionalization with time reversal symmetry in 2D graphenelike systems 25,26 , leading to the formation of states with topological properties 27,28 . There is no experimental evidence yet of the Kek-O phase in graphene 20,29 , although it can be achieved in analogues systems like molecular graphene 21 and vibrational systems 30 . As for the Kek-Y phase, it became a subject of scrutiny after its recent experimental realization by C. Gutierrez, et al 31 , whom showed amazing STM images of standing-wave in the local density of states of graphene on Cu(111) surface forming a Kek-Y pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations are performed using first-principle theory imbedded in the QUNTUM ESPRESSO code [17]. The Perdew-Burke-Ernzerhof generalized gradient approximation (PBE-GGA) functional is employed and the pseudopotential is ultrasoft [18,19]. We have also verified the GGA with the Van der Waals forces correction and the result differences are negligible.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…In graphene, bond modulations can be induced by local changes in the position of the carbon atoms due to the absorption of adatoms on its surface [32] or by a proximity effect [33,34]. One such example is the KOC modulation, depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%